A Web-Based Auditory and Visual Emotion Perception Task Experiment With Children and a Comparison of Lab Data and Web Data - Yamamoto, Hisako W.; Kawahara, Misako; Tanaka, Akihiro (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, the significance of online research has been rising in the field of psychology. However, online experiments with child participants are rare compared to those with adults. In this study, we investigated the validity of web-based experiments with child participants 4–12 years old and adult participants. They performed simple emotional perception tasks in an experiment designed and conducted on the Gorilla Experiment Builder platform. After short communication with each participant via Zoom videoconferencing software, participants performed the auditory task (judging emotion from vocal expression) and the visual task (judging emotion from facial expression). The data collected were compared with data collected in our previous similar laboratory experiment, and similar tendencies were found. For the auditory task in particular, we replicated differences in accuracy perceiving vocal expressions between age groups and also found the same native language advantage. Furthermore, we discuss the possibility of using online cognitive studies for future developmental studies.